O agroextrativismo nas feiras livres e comunidades rurais: estudo sobre coleta e comercialização de produtos da natureza no Alto Jequitinhonha - Danilo Marinho Lamêgo Borges (2019)
The main objective of this Thesis is to analyze the importance of products that come from agroextractivism to family farmers from the territory of Alto Jequitinhonha. The research conducted had an exploratory nature, employing quantitative and qualitative techniques. The applied method was case study, multiple case study design. The field research has been performed in two stages. The first has been performed by NPPJ’s and Vicente Nica Alternativa Agriculture Center (CAV) research teams, which has provided all the original data for this Thesis. These data has been collected in six rural communities from the municipality of Turmalina (Gentio, Tanque, Poço D’Água, José Silva, Campo Alegre and Campo Buriti.), sampling around 10% of families in each one of the communities. In the second stage of the research, developed by the author with the support of the research team, a survey on agroextrativism’s products was made during the period of one year on street markets in the cities of Chapada do Norte, Itamarandiba, Minas Novas, Turmalina and Veredinha with both marketers and mediators who perform the commercialization of products from agroextractivism, using a a semi-structured research guide. The results of this Thesis show that rural communities researched in Turmalina collect a great range of native fruits, but only a few of them are commercialized at the free markets in study. Among them, the pequi, mangaba, gabiroba and jatobá stand out, but the destination given to the majority is the families’ own consumption. Although the free markets have only part of collected production for sale, they present relevant offer of agroextractivism’s products: from December of 2018 to December of 2019, 60 products from agroextractivism that are commercialized on the markets were mapped, and each municipality presented a diverse behavior about the offer. In all of the markets, the product with the biggest percentage of points of sale has been the pequi and its derivatives, which correspond to 64.16% os the products quantified during all research on free markets. Other products have also been observed, as the range of native fruits, manufactured florestal products, unconventional food plants (UFPs), medicinal plants, among other diverse products. As a result, it is assumed that agroextractivist has great relevance for family farmers on the five municipalities. The variety of products with food or medicinal purposes, utensils and tools show that the agroextractivist production is something inherent on Vale do Jequitinhonha’s family farming.